PENGELOLAAN AGROWISATA BUAH NAGA SEBAGAI WISATA ALTERNATIF DI LEMPONGSARI SLEMAN YOGYAKARTA - Priyono, Andiko; Astuti, Widyarini (Kepariwisataan: Jurnal Ilmiah, 2016)
The tourism sector is one of the assets owned by each region in Indonesia. In Yogyakarta, there are agricultural or agro tourist established by PT. Bona Mitra Multifarm, Agrotourism is located at Jl. Jengger lempongsari Sleman Yogyakarta is used as an alternative tourism because no large-scale construction and do not damage the environment. Agrotourism is already running two years and has an area of 2 hectares with the main plant is dragon fruit, here there are three types of dragon fruit is r ed, yellow and white. Dragon fruit is chosen because it has economic value which is quite high when compared with other fruit, other than that the Dragon Fruit has enough health giving properties such as balancing blood sugar levels, purify the blood. Strategies in the management of agrotourism as a new alternative object in Sleman, such as maximizing the knowl e dge of management and communicating between all management and society. The need for the provision af the allocation of funds for the provision of facilities, provide conseling to peoples who don’t understand about agrotourism, seek operating funds from the central office for security improvements such as fencing garden. In supporting the advancement of society agrotourism around also has an important role as well as maintain the security and comfort of tourists that visit here, friendly, open food stalls, juice, puls counter, and angkringan outside agrotourism area. Except that, around of agrotourism any accommodating facility build by others industries, so that it should be aacility for tourist accommodation that visit to this agrotourism. Keywords: Alternative Tourism, Agrotourism, Dragon Fruit, Yogyakarta